A systematic approach to design and analysis of antennas on complex platforms. - Paynter, G.F (IEEE Antennas & propagation magazine.)
The expansion in terrestrial and space communications often requires antennas to be installed in very confined areas on a tower or spacecraft. Since installation and structure variables increasingly dominate the overall communications system performance, an analysis of such structures can be very important. The structures of interest are often in the near field of the antenna, but most antenna design and analysis tools produce far-field results. A common satellite communications scenario involves scatterers such as solar panels or support structures that degrade antenna performance, especially if either the scatterers or the antenna can move in relation to each other. A systematic design and analysis approach that uses several well-known techniques in a cooperative design environment is presented, and illustrated using a scenario